Diseño del programa de salud ocupacional y seguridad industrial para la empresa GRAM ingeniería y construcciones Ltda. (2013)
Through this document, we mean to present a proporal so as to design a labour health and industrial security program for gram ingenieria y construcciones ltda. For this purpose, there are several effective policies that will aim to, either partially or totally, diminish and eliminate all of thore risk factors, which threaten the wellbeing of gram ingenieria y construcciones ltda, since most of its personal (electric, technicians, operative staff, as well as managers) are under different risk levels. Therefore it´s worth to take into account that labour diseases, even accidents are evidently some aspect that meaningfully affect the smooth development of daily activities within the company. Moreover, they create a negative impact on productiveness and working routines. Consequently, this program shows up as a prevention method within the factory, which will avoid the loss of economic resources eith for rehabilitation or indemnification due to diseases or accidents which, conveniently, might be avoided or reduced through a labour health and industrial security program